Perspectives of a mobile intervention for kidney transplant seekers: Post-intervention qualitative results from the KidneyTIME study - Liise K. Kayler; Anne Solbu; Maria Keller; Matthew Handmacher; Ekaterina Noyes; John Von Visger; Thomas H. Feeley; Laurene Tumiel-Berhalter; Renee B. Cadzow (PLoS ONE, 2025)
Objective Mobile health education could expand accessibility, but limited research has explored attitudes about such products among kidney transplant (KT) seekers. This study aimed to assess KT-seeker’s attitudes about the learning and donor search intervention in the KidneyTIME study, which examined the effectiveness of a web-based intervention leveraging animated video education, video viewing and sharing, and use-reminders compared to usual care video alone. Methods Among 56 unique intervention-arm patients (54% non-Hispanic White, 58% no college degree, 46% total annual household income ≤ $30,000), we conducted semi-structured individual interviews with 31 patients and collected open-box survey comments from 36 patients. Using content analysis, we analyzed transcripts of the interviews to identify key concepts related to patient experience and usage of the mobile program as well as suggested improvements. Results Most patients found the online program to be convenient and easy to access on any device, although a few recommended technological enhancements or availability earlier in the transplant process. The video content was helpful to learn and reduce anxiety about kidney transplantation and donation; additional topics were suggested and that it could be more personalized. Videos were shared to put others at ease, prepare them, and elicit possible donors. Some could have benefitted from sharing instructions or assistance or wanted other outreach modalities. The digital reminders to use the resource prevented forgetting and prompted watching. Conclusion Patients had positive feelings about KidneyTIME, including receiving information from animated videos, sharing videos with their social network, and receiving email or text reminders. Findings provide insights about patients’ experience with this innovative approach for providing self-education and empowering patients’ social network outreach about kidney transplantation and donation, including future enhancements to consider.